2005
DOI: 10.1590/s0004-282x2005000300016
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do Bromazepam observados pela eletroencefalografia quantitativa (EEGq) durante a prática de datilografia

Abstract: Effects of Bromazepam in qEEG by typingwritingABSTRACT -The efficiency with which an information is processed by the brain's neural circuitry can be altered by neuromodulators. The use of Bromazepam in the pharmacological treatment of anxiety disorders is due to its anxiolytic property. However, the effects of this benzodiazepine in motor learning tasks are not entirely understood. In this context, the goal of this study was to assess the effects of Bromazepam ( 6 m g ) on psychophysiological, behavioral, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…These experiments contribute to the comprehension of differences between times 1 and 3. In behavioral studies, a reduction in mistakes and execution time during typewriting is also observed 26 . These findings reinforce the hypothesis that the transition from block 1 to 2 seemed to match with some critical stage of learning; setting, perhaps, the evolution from a controlled processing stage (emphasizing on cognitive demands), toward advanced stages, such as automatism (predominantly motor demands).…”
Section: Discussionmentioning
confidence: 91%
“…These experiments contribute to the comprehension of differences between times 1 and 3. In behavioral studies, a reduction in mistakes and execution time during typewriting is also observed 26 . These findings reinforce the hypothesis that the transition from block 1 to 2 seemed to match with some critical stage of learning; setting, perhaps, the evolution from a controlled processing stage (emphasizing on cognitive demands), toward advanced stages, such as automatism (predominantly motor demands).…”
Section: Discussionmentioning
confidence: 91%
“…Estudos envolvendo a prática motora mostram que conforme a atividade é repetida ocorre melhoria nas variáveis comportamentais, ou seja, o sujeito executa a tarefa de maneira mais ágil e precisa. Alterações nestas variáveis sugerem aprendizagem e evidenciam alterações plásticas decorrentes da fi xação da tarefa motora [40][41]. Alguns autores, no intuito de verifi car quais componentes de um programa de exercícios são mais efi cazes na redução do risco de quedas, realizaram várias abordagens de tratamento variando em freqüência, intensidade e duração.…”
Section: Resultsunclassified
“…Beta is considered a fast wave frequency (12 to 30 Hz) and appears to be the one that is most related to motor activities, both premotors and motor itself, having value for analyses related to normal and pathological movements. The theta frequency band is associated with automatism and attention processes, as well as being important for a variety of cognitive functions [11,12].…”
Section: Introductionmentioning
confidence: 99%